Inside Cover. Issue 5 (24th April 2022) - Zhang, Mingchao; Tao, Yue; Chang, Qing; Wang, Kaixuan; Chu, Tianqing; Ying, Weihai
Abstract : The skin's green autofluorescence (AF) at the Dorsal Centremetacarpus of lung cancer patients was significantly higher than that of healthy subjects and pulmonary infection patients. Using the AF intensity as the variable, ROC analyses showed that the AUC for differentiating the lung cancer patients and the pulmonary infection patients was 0.87, suggesting that the skin's AF may become a novel biomarker for non‐invasive and economical diagnosis of lung cancer. Further details can be found in the article by Mingchao Zhang, Yue Tao, Qing Chang, Kaixuan Wang, Tianqing Chu, and Weihai Ying (e202100389 ) Abstract : The skin's green autofluorescence (AF) at the Dorsal Centremetacarpus of lung cancer patients was significantly higher than that of healthy subjects and pulmonary infection patients. Using the AF intensity as the variable, ROC analyses showed that the AUC for differentiating the lung cancer patients and the pulmonary infection patients was 0.87, suggesting that the skin's AF may become a novel biomarker for non‐invasive and economical diagnosis of lung cancer. Further details can be found in the article by Mingchao Zhang, Yue Tao, Qing Chang, Kaixuan Wang, Tianqing Chu, and Weihai Ying (e202100389 )